Working safely in small enterprises in Europe: towards a sustainable system for worker participation and representation - Walters, David (Brussels, 2002)
"Equality in health and safety in workplaces of all sizes is a key trade union demand. The Community directives lay down the same obligations for all workplaces, but the data collected reveal that compliance varies widely with the size of the firm. Commitment from all stakeholders, both inside and outside the workplace, is essential to improve the management and level of health and safety in small and medium-sized firms. Worker participation is fundamental to that, but too often it is lacking or non-existent. The unions have a key role in promoting and supporting worker participation and representation in health and safety in small firms. This report, written for a project run with trade unions in different EU countries, evidences that a wide range of national systems for representation exist - as well as inequalities created by the form they take and how they are applied - but also that new practices are growing up."